Effects of agro-forestry systems on the physical and chemical characteristics of green coffee beans - Virginio Filho, Elias de Melo; y otros 7 autores más (Frontiers, 2023)
A study at CATIE, Costa Rica, examined 20 agroforestry systems for coffee plantations, testing different management practices and shade types. Physical and chemical attributes of green coffee beans were analyzed. Full sun and Erythrina shade trees improved bean density, reduced moisture and roasting loss. Intensive organic management increased mineral content (K, P, Ca). Full sun systems also promoted minerals (Ca, Mn). Intensive organic management and Erythrina shade trees increased total lipid and fatty acid contents. Caffeine content was higher with intensive conventional and organic management and in full sun systems. Erythrina shade trees improved carbohydrate content. For sustainability, combining intensive organic management with Erythrina shade trees was recommended for local coffee farmers.